Women Who Sell Sex in Eastern and Southern Africa: A Scoping Review of Non-Barrier Contraception, Pregnancy and Abortion - Catriona Ida Macleod; John Hunter Reynolds; Richard Delate (Frontiers Media S.A., 2022)
Objectives: There is a need to hone reproductive health (RH) services for women who sell sex (WSS). The aim of this review was to collate findings on non-barrier contraception, pregnancies, and abortion amongst WSS in Eastern and Southern African (ESA).Methods: A scoping review methodology was employed. Inclusion criteria were: 1) empirical papers from 2) ESA, 3) published since 2010, and 4) addressing WSS in relation to 5) the identified RH issues.Results: Reports of rates of non-barrier contraceptive usage varied from 15% to 76%, of unintended pregnancy from 24% to 91%, and of abortion from 11% to 48%. Cross-cutting factors were alcohol use, violence, health systems problems, and socio-economic issues. Pregnancy desire was associated with having a non-paying partner. Barriers to accessing, and delaying, antenatal care were reported as common. Targeted programmes were reported as promoting RH amongst WSS.Conclusion: Programmes should be contextually relevant, based on local patterns, individual, interpersonal and systemic barriers. Targeted approaches should be implemented in conjunction with improvement of public health services. Linked HIV and RH services, and community empowerment approaches are recommended.